Preparation of a single metal catalyst loaded on alumina support to refine waste tire pyrolysis oil (WTPO) via catalytic hydrogenation - Sinurat, S.; Hafriz, R.S.R.M.; Habib, S.H.; Salmiaton, A.; Izhar, S.; Hamid, M.R.A.; Sobri, S.; Razali, N.M. (Elsevier, 2023)
Improper disposal of industrial waste, particularly non-biodegradable solid waste like waste tires, has long been a significant environmental concern. Despite this, waste tires can be converted to fuel as alternative source through pyrolysis. However, waste tire pyrolysis oil (WTPO) has limitations, such as high sulfur content, making it unsuitable for direct use as a fuel. This research aims to improve the quality of waste tire pyrolysis oil (WTPO) by catalytic hydrogenation. Using modified metal catalysts, including nickel, cobalt, ammonium molybdenum, and alumina as supporting substances. The catalyst was synthesized using the impregnation method and subsequently subjected to calcination. The catalyst performance was evaluated by conducting the hydrogenation reaction. The catalytic hydrogenation reaction results indicate that the catalyst Mo/Al2O3 exhibited the best performance in producing refined oil. The refined oil was desulfurized to a sulfur compound of 0.7 wt at 320 ◦C under the flow rate of the gas of 100 ± 50 cm3/min, which corresponded to a sulfur reduction of 75 compared to the initial feedstock. Interestingly, while the non-catalytic reaction presented the highest performance towards sulfur removal of 80, it was inferior towards the selectivity of benzene, D-limone and p-cymene.